A Young Lady’s Passion for Cats: Sun Sunyi and Three Qing Compendia on Cats - He, Jianjun (JAOS, 2025)
In addition to large book projects sponsored by the state, compendia and encyclopedias were also popular individual scholarly endeavors among Ming and Qing intellectuals. This article focuses on one Qing compendium on cats, Xianchan xiaolu 銜蟬小錄, authored by a seventeen-year-old female named Sun Sunyi 孫 蓀意 (1783-1818). Through a detailed examination of Sun Sunyi’s collection and classification of texts concerning cats, as well as a comparison with two other compendia on cats compiled by male scholars, I argue that Xianchan xiaolu, distinctively marked by the editor’s age, gender, and personal interests, presents not only valuable information for the study of the late imperial textual tradition and the role of scholarship in literary writings but also an important and joyful case for increased research on female participation and reception in Qing intellectual trends.